Idiom Adventures for Young Explorers, strengthening English language competence in 4th graders (2024)
This work aims to strengthen the lexical competence of fourth-grade students at Liceo Manantial de Vida in Bogota by designing a Virtual Learning Environment (VLE), focusing on idiomatic expressions in the classroom context. The adapted approach promotes contextualized learning, linking theoretical vocabulary knowledge and its practical application. Material is designed to strengthen lexical competence in English, using idiomatic expressions in the classroom and thus advancing the teaching-learning process.